Patients with longstanding ulcerative colitis in remission do not have more irritable bowel syndrome-like symptoms than controls. Issue 1 (December 2016) - Lundgren, D.; Rutegård, J.; Eklöf, V.; Palmqvist, R.; Karling, P.
Abstract Background Irritable bowel syndrome (IBS) is more common in patients with ulcerative colitis (UC) than expected. The prevalence of IBS in patients with UC with longstanding disease is not known. We investigated the prevalence of IBS-like symptoms in patients with UC in remission and longstanding disease in comparison to control subjects. Methods Sixty-eight patients with UC and 33 patients with hereditary familiar colon cancer and who underwent colonoscopy surveillance were included. Faecal calprotectin (FC), Gastrointestinal Symptoms Rating Scale-Irritable Bowel Syndrome (GSRS-IBS) and Hospital Anxiety and Depression scale were fulfilled prior to endoscopy. UC in remission was define by steroid-free clinical remission, a Mayo Score ≤ 1 on endoscopy, a FC ≤ 200 μg/g and no significant active inflammation on colon biopsies. Results Fifty-five UC patients met the criteria for being in remission. The median disease duration was 17 years. The patients with UC in remission tended to have lower scores on total GSRS-IBS score (6 vs 10.5;p = 0.062) and lower or equal scores on all specific IBS symptoms in comparison to controls. There was a moderate but significant correlation between diarrhoea scores and FC levels (in the span ≤ 200 μg/g) (rs 0.38;p = 0.004) in the UC in remission group. Conclusion Patients with UC with longstanding disease and in remission do not have more IBS symptoms than controls. In UC patients in remission the FC level in the lower span showed a moderate correlation to symptoms of diarrhoea.